Effect of deep eutectic solvent in proton conduction and thermal behaviour of chitosan-based membrane - Wong, C. Y.; Wong, W. Y.; Walvekar, Rashmi; Loh, K. S.; Khalid, Mohammad *; Lim, K. L. (Elsevier, 2018)
This work aims to study the effect of choline chloride (ChCl) and urea based deep eutectic solvent (DES) on the proton conduction and thermal properties of chitosan-carboxymethylcellulose (Chitosan-CMC) membrane. Chitosan-CMC biocomposites were prepared in different ratios of 5:95, 10:90, 25:75, 50:50 and 75:25 with DES and was characterised. This study showed a positive improvement the proton conductivity without excessive swelling using DES in comparison with those without DES, with a slight trade-off on the thermal stability. The sample corresponding to 50 wt% of chitosan showed the highest proton conductivity of 1.57 × 10−2 S/cm, which was slightly lower compared to Nafion-117 membrane (8.6 × 10−2 S/cm). The study revealed the blend film with 75 wt% of chitosan with the presence of DES has a potential for polymer electrolyte membrane (PEM) with a low but sufficient water uptake of 49.4% to avoid structural disintegration despite a lower proton conductivity obtained.